Iron deficiency anaemia is common in patients with an ileoanal pouch and is not always associated with inflammation. (13th March 2011) - Jaboli, M F; Hamilton, M; Marelli, L; Toumpanakis, C; Erian, G; Epstein, O; Murray, C
Abstract : Introduction: Ileal pouch anal anastomosis (IPAA) is the standard restorative procedure for ulcerative colitis (UC) following colectomy. This operation is, however, associated with distinct rates of failure and complications. Iron deficiency anaemia (IDA) is common in this group of patients although it is not clear to what degree this is secondary to ongoing inflammation or other mechanisms. The authors therefore performed a systematic audit of the patients after restorative proctocolectomy coming to the Inflammatory Bowel Disease (IBD) Clinic in our department. Methods: 74 patients (37 male, 37 female, mean age 47 years) with IPAA were recruited from the Inflammatory Bowel Disease Clinic. Demographic and medical data were collected retrospectively from medical notes. Clinical signs of pouchitis were increased stool frequency, urgency, tenesmus, incontinence, abdominal pain, pelvic discomfort and nocturnal seepage. Results: Among 74 patients with IPAA and IBD (66 patients with UC, 4 Crohn's disease and 4 indeterminate colitis), 24 patients (30%) had anaemia and/or low iron indices. Seven of these 24 patients (30%) had clinical signs of pouchitis, two had β-thalassemia and one celiac disease. A sigmoidoscopy of the pouch was performed in 56 of the patients (75%). Only 23 patients had an oesophageal-gastro-duodenal endoscopy (OGD) but of the remaining 51 patients, 20 had negative antitissue transglutaminases antibody (TTG). The OGDs were all normal, including the duodenal biopsies. The authors performed capsule endoscopy in 11 patients with anaemia: 4 patients had small bowel erosions, 5 patients had erosions at the anastomotic site (4 with active bleeding), 2 had pouchitis, 1 angiodysplasia and 1 was normal. Considering all 75 patients with IPAA, 37 patients developed pouchitis (50%), 5 fistula (7%), 2 had PSC (4%), 2 of whom had OLT. Conclusion: In this series of patients who underwent IPAA, nearly one third developed anaemia. In these patients, the most common findings at capsule endoscopy were erosions in the small bowel and at the anastomosis, which though contributory are unlikely to represent the cause of their anaemia. The most frequent complication in this group of anaemic patients was pouchitis. This audit suggests that iron deficiency anaemia is common in patients with IPAA and that further studies are required to investigate the mechanism of iron deficiency in this particular group of patients.